The garage in entrepreneurship and innovation: Four archetypes - Pina e Cunha, M.; Sarkar, S.; Rego, A.; Gaim, M. (Entrepreneurship Research Journal, 2025)
This paper explores the role of the garage in entrepreneurship and innovation. By engaging sociomaterial and symbolic views, it develops a typology that aims not to repeat an overly romantic view of the garage as the space where lone heroic entrepreneurs start their ventures in idealized seclusion from the rest of humanity nor to dismiss it as a flawed, useless idea. By discussing four archetypes, the paper complexifies the notion of the garage as a space that can be material as well as symbolic and proposes how organizations can recreate ‘garages’ in their habitual workspaces.